High temperature pyrolysis of lignite and synthetic carbons. (1st April 2019) - Apicella, B.; Russo, C.; Ciajolo, A.; Cortese, L.; Cerciello, F.; Stanzione, F.; Wuetscher, A.; Muhler, M.; Senneca, O.
Abstract: The paper explores changes in reactivity and chemico-physical characteristics of char and tar produced by severe heat treatment of lignite in both inert atmospheres and CO2 rich atmospheres. The role of mineral matter, in particular metal oxides, in catalysing chemical and physical transformations is also addressed. A Rhenish Lignite from the Garzweiler mine was studied and compared with: a) mineral-free synthetic carbon (HTC), obtained from cellulose; b) a synthetic carbon doped with iron oxide (Fe2 O3 ). A heated strip reactor (HSR) was employed at temperatures of 1300 and 1800 °C in N2 and CO2 atmospheres. Liquid and solid products (tar and char) were analysed and compared. Tar composition was evaluated by extraction and gas chromatography-mass spectrometry, whereas the solid carbonaceous material produced by pyrolysis, mainly composed of char, was characterized regarding its thermal behaviour by thermogravimetric analysis and its structure by Raman spectroscopy and scanning electron microscopy. Results show that iron oxide exerts a catalytic influence on both pyrolysis and char oxidation. Upon severe heat treatment, it reduces char reactivity promoting graphitization and structural ordering. The overall effect on char reactivity is therefore not easy to predict.